A scanning tunnelling microscopy study of Clostridium pasteurianum rubredoxin - Mukhopadhyay, R; Davis, J; Kyritsis, P; Hill, H; Meyer, J (2000)
Scanning tunnelling microscopy (STM), which can provide 'direct' and 'non-averaged' information on molecular structure in three dimensions, has been used to achieve sub-molecular resolution in a 'single molecule' of rubredoxin, an important iron-sulphur protein, at the gold (111) | water interface. The metal-ligand site [Fe (III)-Cys4] appears distinct because of an enhancement of the tunnelling current over this region compared to the surrounding protein structure. © 2000 Elsevier Science Inc. All rights reserved.